2000
DOI: 10.1002/hep.510310224
|View full text |Cite
|
Sign up to set email alerts
|

Support of sinusoidal endothelial cell glutathione prevents hepatic veno-occlusive disease in the rat

Abstract: Depletion of sinusoidal endothelial cell glutathione (GSH) has been proposed as a common mechanism leading to hepatic veno-occlusive disease (HVOD). This study examines whether intraportal infusion of GSH can prevent HVOD in the monocrotaline rat model. HVOD was induced in rats with monocrotaline 160 mg/kg i.g. on day 0. GSH was infused intraportally by mini-osmotic pump. Monocrotaline decreased GSH in sinusoidal endothelial cells, but not in liver homogenate. Infusion of GSH, 2 mol/hr starting day Ϫ 1, preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
76
1
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(83 citation statements)
references
References 9 publications
5
76
1
1
Order By: Relevance
“…16 Monocrotaline administration produces a VOD-like lesion in rats. 17 In this experimental model, damage to SECs precedes evidence of parenchymal cell toxicity and appears to relate to SEC glutathione. Depletion of glutathione sensitizes animals to monocrotaline, and constant infusion of glutathione or N-acetylcysteine during monocrotaline administration prevents the injury.…”
mentioning
confidence: 77%
“…16 Monocrotaline administration produces a VOD-like lesion in rats. 17 In this experimental model, damage to SECs precedes evidence of parenchymal cell toxicity and appears to relate to SEC glutathione. Depletion of glutathione sensitizes animals to monocrotaline, and constant infusion of glutathione or N-acetylcysteine during monocrotaline administration prevents the injury.…”
mentioning
confidence: 77%
“…Previously reported work demonstrated that hepatic glutathione was significantly decreased in alcoholic liver disease [44] , hepatic veno-occlusive disease [45] , chronic hepatitis C [46] , Wilson's disease [47] and other liver-related diseases. The significant depletion of hepatic glutathione in the OP rats was a marker of the disruption of cellular redox status related to CKD-induced liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…Animals treated with N-acetyl-L-cysteine were protected against monocrotaline-induced hepatic VOD as shown by less histological changes and clinical manifestation. 23 The cellular content of GSH may be modulated in vitro and in vivo by different treatments. 24 Precursors of GSH, such as methionine or N-acetyl-L-cysteine (NAC), increase the cellular content of GSH.…”
mentioning
confidence: 99%